1956
DOI: 10.1149/1.2430288
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Overvoltage in Concentrated Acid Solutions

Abstract: Oxygen overvoltage was measured on platinum electrodes in 5M perchloric acid from -45 ~ to +40~ and in 0.005-9M perchloric acid at 0~ A limiting current density that was found is due to activation overvoltage at the anode surface. This limiting current density decreased at lower temperatures and in higher perchloric acid concentrations. It also marked the beginning of ozone formation. Adsorption of perchlorate ions is bebelieved to be the cause of the limiting current density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

1958
1958
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Figure 3 shows a limiting current-density region where the limiting current density decreases with increasing salt concentration. A similar result has been obtained for platinum electrodes in concentrated perchloric acid solutions and it is suggested that adsorption of perchlorate ions is believed to be the cause of the limiting current [14]. The transition range between the upper and lower Tafel lines begins at a potential decreasing slightly with increasing perchloric acid concentration and finishes at a potential decreasing strongly with increasing perchloric acid concentration.…”
Section: Mechanism For Perchlorate Formationsupporting
confidence: 79%
See 2 more Smart Citations
“…Figure 3 shows a limiting current-density region where the limiting current density decreases with increasing salt concentration. A similar result has been obtained for platinum electrodes in concentrated perchloric acid solutions and it is suggested that adsorption of perchlorate ions is believed to be the cause of the limiting current [14]. The transition range between the upper and lower Tafel lines begins at a potential decreasing slightly with increasing perchloric acid concentration and finishes at a potential decreasing strongly with increasing perchloric acid concentration.…”
Section: Mechanism For Perchlorate Formationsupporting
confidence: 79%
“…Analogously to an electrolysis of a perchlorate solution [14], it is assumed that for an electrolysis of chlorate the point of inflection of the curve connecting the upper and lower Tafel lines represents the point where chlorate ion discharge begins. The potential of the inflection point is much higher for perchlorate solution than for a chlorate solution [15] and the current density for oxygen evolution at the inflection potential is much higher for a perchlorate solution than for a chlorate solution (Fig.…”
Section: Mechanism For Perchlorate Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases, these peroxide structures undergo either a partial chemical decomposition yielding oxygen or act as intermediates in ozone formation. The yield of the latter increases with the acid electrolyte concentration [17] . As a matter of fact, the onset of thick film growth on gold becomes appreciable above about 2 V in a potential region where a linear Tafel behaviour is observed for the oxygen evolution on gold [5,16,18] .…”
mentioning
confidence: 92%
“…Such a fact can be explained through the formation of peroxide species, which in the case of platinum is related to the Pt0 2/Pt0 3 redox couple (E°=2 .1 V) [14] . For gold, peroxide species are detected when the potential is already in the vicinity of the potential where the O-monolayer electroadsorbed on gold is practically completed [5,17] . In both cases, these peroxide structures undergo either a partial chemical decomposition yielding oxygen or act as intermediates in ozone formation.…”
mentioning
confidence: 99%